Effective Farm Business Strategy for Local Commodities in Haiti; Case of Maize - Rival Valcin; Tomohiro Uchiyama (Études Caribéennes)
Low productivity seems to be the biggest issue faced by the Haitian farming. Besides, previous studies concluded that this problem is due specifically to inadequate or poor quality of input used by the farmers. The economic condition of the farmers prevents them from even meeting the crop calendar. This study suggests that boosting the agricultural investment by the mean of contract farming to promote the access to an improved package of technologies, would be an effective strategy to overcome the current situation. The results show that the adequacy of the package of technologies has a significant influence on the productivity. Furthermore, as a new phenomenon for Haiti, the contract farming benefits a high level of willingness from the Haitian farmers. In addition, the farmers with low annual income and/or greater area cultivated seem to be more likely to accept the contract farming.